In Search of Growth Effects by inward FDI in Central East Europe - Johannes Stephan; Olivier Zieschank (European Regional Science Association (ERSA), 2012)
With systemic change in Central East European countries (CEECs), foreign direct investment (FDI) became an important factor for the transition economies. FDI not only played a leading role in privatisation in most transition countries. FDI is also widely assumed to spur restructuring in terms of capital and technology transfer, spillovers, breaking up of national monopolies, and alignment of sectoral specialisation to comparative advantages. This way, FDI is often entrusted with a leading role in the growth and development processes in CEECs. Alas, empirical proof of FDI's positive contributions to macroeconomic growth remains not robust in an already large body of literature: significant positive growth effects are typically only found by use of very complex methods based on neoclassical growth theory and often only in very specific model specifications. For CEECs, the literature is generally overly optimistic, which is not least used by policy makers (and lobbyists) to argue for active FDI-attracting policies. This contribution revisits the FDI-growth-contribution hypothesis for the case of CEECs during the last 15 years with a particular focus on the individual roles of financial sector FDI and manufacturing industry FDI. The analysis uses the clearest and simplest econometric set-up in the form of a Cobb-Douglas production function that distinguishes between FDI flows and stocks and controls for policy-interventions, human capital endowments, technological activity of firms, and for heterogeneity between countries, sectors, and years. Applying a very large number of alternative models and specifications and post-estimation tests, the analysis concludes for CEECs (i) that there is no robust and convincing independent and effect of neither financial nor manufacturing nor total inward FDI on economic growth if assumed to work via accelerating technical advance (the A in AK-models) in a neoclassical world; and (ii) that robust positive growth contributions become much more convincing as soon as neoclassical assumptions are relaxed, and FDI can affect growth via capital, human capital, and capital formation. For future empirical analysis, this suggests that the search for growth effects by inward FDI in CEECs as economies in transition has to consider indirect effects beyond the strict conceptualisation of neoclassical or new growth theory. For economic policy, the results suggest that FDI may have positive growth effects, but only indirect ones, necessitating a policy-mix beyond the pure attracting of more inward FDI.
Keywords: 330